Mathematics achievment in the division achievement test of grade VI pupils taught in the mathematics teachers Association of the Philippines Approach and in conventional approach of Taguig III District, Division of Taguig and Pateros, School Year 2001-2002: an evaluation - Bisco, Cipriano L. Jr.; Paulino, Lina B. Capinpin, Dominador (Parañaque City: Olivarez College, 2002)
The study tried to evaluate the effectiveness of the Mathematics Teachers Association of the Philippines (MTAP) teaching approach in Mathematics among the Grade Six pupils in Taguig ll District, Taguig School Year 2001-2002? our Almighty Father Pateros Division during the blessings ar ce to finale vestiment of Parents Specifically, it tried to answer the following questions/problems: 1. How are the Grade Six pupils taught in the Mathematics Teachers Association of the Philippines teaching approach and in the traditional approach described when grouped according to: 2. How are the pupils taught in the Mathematics Teachers Association of the Philippines teaching approach and in the Conventional approach perform in the Division Achievement test by: Family monthly income Educational Attainment of parents Number of study hours devoted to Math per day Frequency of supervised home study by parents.
Master Thesis